Synergistic antibacterial and anti-biofilm activity of nisin like bacteriocin with curcumin and cinnamaldehyde against ESBL and MBL producing clinical strains. Issue 6 (8th August 2020) - Sharma, Garima; Dang, Shweta; K, Aruna; Kalia, Manjula; Gabrani, Reema
Abstract: Bacteriocins are small peptides that can inhibit the growth of a diverse range of microbes. There is a need to identify bacteriocins that are effective against biofilms of resistant clinical strains. The present study focussed on the efficacy of purified nisin like bacteriocin-GAM217 against extended spectrum β-lactamase (ESBL) and metallo-beta-lactamase (MBL) producing clinical strains. Bacteriocin-GAM217 when combined with curcumin and cinnamaldehyde, synergistically enhanced antibacterial activity against planktonic and biofilm cultures of Staphylococcus epidermidis and Escherichia coli . Bacteriocin-GAM217 and phytochemical combinations inhibited biofilm formation by >80%, and disrupted the biofilm for selected ESBL and MBL producing clinical strains. The anti-adhesion assay showed that these combinatorial compounds significantly lowered the attachment of bacteria to Vero cells and that they elicited membrane permeability and rapid killing as viewed by confocal microscopy. This study demonstrates that bacteriocin-GAM217 in combination with phytochemicals can be a potential anti-biofilm agent and thus has potential for biomedical applications.